Langerhans Cell Histiocytosis - A Case Report - Gurubacharya, SM; Gurubacharya, RL (Journal of Nepal Paediatric Society, 2009)
Histiocytosis is a heterogenous group of disorders that are characterized by proliferation and activation of mononuclear phagocyte system. Langerhans Cell Histiocytosis (LCH) or Class I histiocytosis is a rare disorder of unknown etiology with proliferation of Langerhan cells which may infiltrate a single or multiple organs. This disease is more common in infants and children. It is usually sporadic but a familial pattern is known. The term embraces the whole clinical spectrum of the disorder from single bone lesions (eosinophilic granuloma) to an aggressive widespread multisystem disease in very sick child (Letterer-Siwe disease) with a wide variety of intermediate forms including the Hand-shuller Christian triad. The cause of LCH is not firmly established and most investigators in the field have long suspected that LCH is immunologic disorder either in its etiology or in its pathophysiology. Recent evidence suggests that LCH is a clonal disorder rather than reactive disease. LCH is classified according to sites of involvement into single system disease and multisystem disease. Single system disease can be either unifocal or multifocal. Multisystem disease can be either without organ dysfunction or with organ dysfunction. Clinical course of LCH with single system disease is usually benign with high chance of survival. However, its clinical course is often unpredictable and patients can experience spontaneous remission and exacerbations. Histiocytic diseases are currently classified by the writing group of the Histiocyte Society in the three classes, namely; Class I: Langerhans Cell Histiocytosis (LCH) Class II: Histiocytosis of mononuclear phagocytes other than Langerhans Cells Class III: Malignant Histiocytic disorders Key words: Langerhans Cell Histiocytosis, Eosinophilic granuloma, Skull, lytic lesion doi:10.3126/jnps.v27i2.1587 J. Nepal Paediatr. Soc. Vol.27(2) p.87-89